2019
DOI: 10.1002/ajhb.23226
|View full text |Cite
|
Sign up to set email alerts
|

Maternal motives behind elective cesarean sections

Abstract: ObjectivesThe World Health Organization recommends a target cesarean section rate of 10‐15%. In recent years, the US has had a nation‐wide rate of 30.3% and some developed countries are even higher. Many factors account for this high rate, but our hypothesis is that women who elect cesarean section do so at least in part because of unallayed fear.MethodsOur sample was comprised of American women of childbearing age who have not given birth but may in the near future. We received 368 online survey responses wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Based on our findings, we suggest that the underlying factors behind individual characteristics (i.e., older age at the time of the last birth, more years spent in higher education) can influence in varying ways and magnitudes women's decision to have a CS performed. Previous research has demonstrated that fear is an important driver in motivating women to opt for a PCS 24 . In the case of our results, older age at the time of birth and presence of medical or non‐medical problems during pregnancy can indeed induce fear, since both of these factors have been shown to potentially impact birth outcomes in a negative manner 25,26 …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Based on our findings, we suggest that the underlying factors behind individual characteristics (i.e., older age at the time of the last birth, more years spent in higher education) can influence in varying ways and magnitudes women's decision to have a CS performed. Previous research has demonstrated that fear is an important driver in motivating women to opt for a PCS 24 . In the case of our results, older age at the time of birth and presence of medical or non‐medical problems during pregnancy can indeed induce fear, since both of these factors have been shown to potentially impact birth outcomes in a negative manner 25,26 …”
Section: Discussionmentioning
confidence: 52%
“…Previous research has demonstrated that fear is an important driver in motivating women to opt for a PCS. 24 In the case of our results, older age at the time of birth and presence of medical T A B L E 3 Descriptive statistics by type of C-section or non-medical problems during pregnancy can indeed induce fear, since both of these factors have been shown to potentially impact birth outcomes in a negative manner. 25,26 On the other hand, more years spent in higher education can imply that these women can have better access to mechanisms-formal or informal-which allow PCS to be performed.…”
Section: Discussionmentioning
confidence: 70%
“…They have also been associated with higher posttraumatic stress symptom levels in women (Beck et al, 2011). Researchers have reported that women across various cultures most commonly request a planned cesarean because of fear surrounding childbirth (Eide et al, 2019; Reyes & Rosenberg, 2019; Ryding et al, 2016). Reasons for this preference are similar to women in general who fear childbirth and include a previous negative birth experience (Ryding et al, 2016), a previous traumatic birth, fear of having an emergency cesarean, a deep-seated fear of childbirth since their early teens, fear of their own or their baby’s life being at risk, extreme pain, lack of control (Eide et al, 2019), depression, a history of abuse (Ryding et al, 2016), and episiotomy/perineal tears (Long et al, 2018).…”
Section: Understanding Fear Surrounding Childbirthmentioning
confidence: 99%
“…Furthermore, a study by Emile found that the fear and anxiety related to vaginal birth overpowers the consequences of a C-section and women opt for elective C-section to avoid the labor pains and messiness of natural birth (Reyes, 2018). Ecker's study found that women often go for an elective C-section as a defensive decision for the reason of having not being ready to bear the labor or risk perception of vaginal delivery, which are often highlighted in media, social interaction, emotions stories/ bad experiences of others (such as cerebral palsy or infant death) (Lake, 2012).…”
Section: Influence Of Knowledge On Decision Making About Caesarian Sectionmentioning
confidence: 99%